دور الاستثمارات العمومية في المشاريع الانشائية في تحقيق أهداف التنمية المستدامة (odd)، دراسة حالة الجزائر - لعمروس, محمد; شنايت, مراد (جامعة الوادي - University of Eloued, 2023)
تهدف هذه الدراسة إلى ابراز دور الاستثمارات العمومية في المشاريع الانشائية، التي تشمل الطرق والجسور والموانئ والسدود وشبكة السكة الحديدية ومشاريع التطهير وغيرها، في تحقيق أهداف التنمية المستدامة، وتعتبر الاستثمارات العمومية أحد أهم أوجه تدخل الدولة في الحياة الاقتصادية. وتشير الدراسات إلى أن المشاريع الانشائية مسؤولة عن تحقيق 90% من أهداف التنمية المستدامة. ويتم تمويل الاستثمارات العمومية في الجزائر بصفة كلية من خلال الميزانية العامة للدولة، أين يجب على الدولة البحث عن طرق تمويل بديلة، خاصة تطوير الشراكة العمومية – الخاصة، وتحسين كفاءة نطام إدارة الاستثمارات العمومية. ويمثل ادماج الأبعاد البيئية في المشاريع الانشائية تحديا حقيقيا من أجل ضمان استدامتها وقدرتها على الصمود مع مرور الزمن. This study aims to highlight the role of public investment in infrastructure projects, which include roads, bridges, ports, dams, rail, sanitation and other projects, in achieving the Sustainable Development Goals. Public investment is considered one of the most important aspects of state intervention in economic life. Studies show that infrastructure projects are responsible for achieving 90% of the SDGs. Investments in Algeria are entirely financed from the general state budget, where the state must seek alternative modes of financing, including the development of public-private partnerships and improving the efficiency of the public investment management system. The integration of environmental dimensions in infrastructure projects is a real challenge in order to ensure their sustainability and resilience over time
The role of public investment in infrastructure projects in achieving the Sustainable Development Goals (SDGs), case study from Algeria
مقال
Keywords: استثمارات عمومية؛ مشاريع انشائية؛ التنمية المستدامة